Szczególne aspekty utraty wartości aktywów w rachunkowości bankowej - Niewiadoma, Maria (Special Aspects of the Backwardness of Value of Assets in Banking Accounting, 2007)
The role of accountancy grows in bank's information system. Banks follow current' legislative changes on external requirements concerning prepared information. They are concerned particularly on the loss of value of assets, reserves and their results which are kept in financial reports for example: of profit and loss account. Banks have to improve information model, staff managing and internal procedures for information purposes concerning utilization accountancy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 401-409